Pengaruh Alat Permainan Edukatif Kereta Musik Terhadap Perkembangan Bahasa Anak Usia 5-6 Tahun - Nurhenti Dorlina Simatupang; Resi Rosalianisa (JECED : Journal of Early Childhood Education and Development, 2021)
Train educational game music is a game of playing musical instruments such as tambourines, harps, saron, maracas, and guitars in the form of train cars which are varied with songs. This study aims to determine the effect of the musical train educational game media on the language development of children aged 5-6 years. The research method used is a quantitative method. The subjects in this research trial were five children aged 5-6 years and 30 PAUD teachers. The results of trials conducted on five children aged 5-6 years, namely before the trial was 26% and increased to 91% after the media trial train educational game. music. This shows that the train educational game music can improve language development and early reading skills of children aged 5-6 years. The validation results from material experts are 90%, media experts are 75%, and the feasibility assessment of 30 PAUD teachers is 93%. From this research, it shows that the train educational game tool music that has been tested on a small scale is valid and feasible. It shows the train game music is effective and has an effect on children's language development and can be applied and has an attraction for early childhood in learning.